Increasing the Public Speaking Skills of Kindergarten Teachers through Master of Ceremony Workshop - Rizkya, Adetya Nor (EduCurio: Education Curiosity, 2024)
Effective communication skills are crucial for educators, especially those working with young children in kindergarten settings. This study aims to explore the impact of a specialized workshop focused on mastering the art of ceremony (MC) on the public speaking skills of kindergarten teachers. The study contributes valuable insights to teacher professional development, emphasizing the significance of tailored communication training for educators. By focusing on enhancing public speaking skills through a Master of Ceremony framework, this research seeks to improve the overall quality of communication. In this study used a Qualitative Descriptive Research Method and using Data Collection Techniques such as Documentation, Observation and Interviews with the research location at PAUD Bina Putra. There 17 participants. This research was able to run smoothly and received very good feedback from the participants. This can be proven by the results of the questionnaire which stated that they more than agreed that the material provided was sufficient to become an MC with 67% of the answered agreed and 25.8% answering neutral. Then the answers from the results of other questionnaires explained that the speaker had presented the material well, so that it was easy to understand and then it could be implemented properly by the participants as evidenced by the number of answers 71% agreed and only 29% answered neutral